PENGENDALIAN KUALITAS PADA KOMPONEN BARREL PENA E7 DENGAN METODE SIX SIGMA DI PT. X - Moses Xanthus; Marcellinus Irvan P; Angelina Laurentcia; Vanessa Stefani; Lithrone Laricha Salomon (Jurnal Mitra Teknik Industri, 2026)
This study analyzes quality control in the production of E7 pen barrel components in the injection department of PT. X, where the Defect rate consistently exceeded 5% from January to September 2025, peaking at 12.30% in July. The Six sigma method was applied through a Project Charter, Fishbone Diagram, FMEA (with the highest RPN values for material drying at 105 and flashing at 96), as well as data analyses such as Pareto charts to identify dominant Defects arising from unstable mold temperature, low injection pressure, and non-uniform cooling. This descriptive quantitative research uses primary data (observations of temperature, pressure, and Defects) and secondary data from company reports, collected through observation, interviews, and analytical tools such as Minitab and Excel for DPMO calculation and reliability validation. The results indicate potential improvements in the efficiency of the main production process (70% of pen output) through the stabilization of machine parameters and the process DPMO value was reported at 310,416 with a sigma level of 1.995, indicating that the process quality remains low. The main improvement solution involves the application of a Cooling conformal channel to the injection mold, which includes the design of a water-cooling system aimed at distributing heat uniformly and reducing sink marks and flash on the thin walls of the barrel.